Intelligent Home Surveillance System for Facial Recognition Using Raspberry Pi - Dr R Dhanalakshmi, Mr.Likith kumar reddy, Mr.Vinay,Mr.Dileep (International Journal of Modern Agriculture, 2020)
In this project we are going to deal with the surveillance and security system using raspberry pi. We are using VGG face algorithm to process and extract the features in the image that help for facial recognition. We also make use of different type of sensors for creating a security system that will send alerts to the email.